A dosimetric evaluation using the Monte Carlo method considering geometric variations of the Iodine-125 seed for brachytherapy - Henrique Santos de Chico; Lucas Verdi Angelocci; Carlos Alberto Zeituni; Carla Daruich de Souza; Sabrina Spigaroli Sgrignoli; Maria Elisa Chuery Martins Rostelato (Brazilian Journal of Radiation Sciences)
The Institute for Energy and Nuclear Research – IPEN-CNEN/SP is uniquely positioned to develop a new source of Iodine-125 for brachytherapy treatment. Therefore, research into the dosimetric process and source design is widely studied. Task Group 43 – TG 43 cites methodologies for dosimetry of sources for brachytherapy, the most used method is Monte Carlo. However, the dosimetric protocol does not mention possible variations in the source geometry after its conception. The investigative focus of the work was to obtain measurements of the Iodine-125 seed during the production stages until completion, quantify them and simulate them using the Monte Carlo method with the MCNP – 4C code, the formalism was in water and a 101x101 matrix was used to calculate the dose point by point. Two variations were chosen: a) seed length; b) nucleus length, using a batch of 100 seeds for each case. 100 simulations were carried out for each variation and one simulation using the reference seed geometry. The following calculations were applied: relative difference to compare variations to the reference; average among the 100 seeds of each batch to calculate the standard deviation. In both cases there was no point that exceeded 4.48% relative difference, and for standard deviation the largest point was 1.6%, while the Type A uncertainty was 0.018% at the largest point.